Single and multiple sevoflurane exposures during pregnancy and offspring behavior in mice. Issue 7 (11th May 2017) - Lee, Soomin; Chung, Woosuk; Park, Haram; Park, Hanwool; Yoon, Seunghwan; Park, Sangil; Park, Jiho; Heo, Jun Young; Ju, Xianshu; Yoon, Seok‐hwa; Kim, Yoon Hee; Ko, Youngkwon
Summary: Background: The second trimester is a period of neurogenesis and neuronal migration, which can be affected by exposure to anesthetics. Studies also suggest that multiple exposures may have a greater impact on neurodevelopment. Aim: We investigated whether in utero single or multiple exposures to anesthetics caused long‐term behavior changes. Methods: Pregnant mice were randomly divided into four groups on gestational day 14 (GD 14). Mice in the Control × 1 group were exposed to 100% oxygen for 150 min. Mice in the Sevo × 1 group were also exposed to 100% oxygen for 150 min, except that 2.5% sevoflurane was added during the first 120 min. Mice in the Control × 3 and Sevo × 3 group were identically treated as Control × 1 and Sevo × 1 group for three consecutive days, respectively (GD 14–16). Behavioral tests were performed only with the male offspring at the age of 2–4 months. Synaptic plasticity was also compared by inducing long‐term potentiation in acute hippocampal slices. Results: Single or multiple sevoflurane exposures in pregnant mice during the second trimester did not cause long‐lasting behavioral consequences or changes in long‐term synaptic plasticity of their offspring. Conclusion: Our study suggests that neither single nor multiple exposures of mice to sevoflurane during the fetal developmental period induces long‐term behavioral dysfunctions or affects long‐term synaptic plasticity. Additional studies focusing on early stages of neurodevelopment are necessary to confirm the effects of sevoflurane exposure during pregnancy. Abstract :